2020
DOI: 10.1002/arch.21687
|View full text |Cite
|
Sign up to set email alerts
|

Noncompetitive tight‐binding inhibition ofAnticarsia gemmatalistrypsins byAdenanthera pavoninaprotease inhibitor affects larvae survival

Abstract: The economic loss in soybean crops caused by the Lepidoptera insects has encouraged the search for new strategies to control this pest, which are currently based on synthetic insecticides. This paper evaluated the ability of ApTI (Adenanthera pavonina trypsin inhibitor) to inhibit trypsin-like proteins from Anticarsia gemmatalis by docking, molecular dynamics, and enzymatic and survival assay. The docking and molecular dynamic simulation between trypsin and ApTI were performed using the program CLUSPRO and NAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 54 publications
0
13
0
1
Order By: Relevance
“…At the kinetic level, SKTI show lower inhibition constant (Ki) compared with those from synthetic inhibitors, which allow them to occupy all the binding sites available in the active centre of the enzyme and thus an optimised adjustment occurs in the enzyme‐inhibitor (EI) complex formation. The synthetic inhibitors, being smaller, do not occupy all the available sites of the enzyme, forming less stable EI complex (Meriño‐Cabrera, de Oliveira Mendes, et al, 2020; Meriño‐Cabrera, Severiche Castro, et al, 2020; Patarroyo‐Vargas et al, 2020; Volpicella et al, 2003). In this study, we found that protein synthesis is accompanied by changes in the insect's enzymes profile.…”
Section: Discussionmentioning
confidence: 99%
“…At the kinetic level, SKTI show lower inhibition constant (Ki) compared with those from synthetic inhibitors, which allow them to occupy all the binding sites available in the active centre of the enzyme and thus an optimised adjustment occurs in the enzyme‐inhibitor (EI) complex formation. The synthetic inhibitors, being smaller, do not occupy all the available sites of the enzyme, forming less stable EI complex (Meriño‐Cabrera, de Oliveira Mendes, et al, 2020; Meriño‐Cabrera, Severiche Castro, et al, 2020; Patarroyo‐Vargas et al, 2020; Volpicella et al, 2003). In this study, we found that protein synthesis is accompanied by changes in the insect's enzymes profile.…”
Section: Discussionmentioning
confidence: 99%
“…Trypsins (EC 3.4.21.4) are serine proteases and are considered the most important digestive proteases of most insects. Trypsins are involved in the initial phase of protein digestion and are characterized by containing a catalytic triad consisting of the amino acid residues Hys, Asp, and Ser; in A. gemmatalis trypsin are Ser 229, Hys 85, and Asp 132 [16,29,30].…”
Section: Trypsin-like Enzymes In Insectsmentioning
confidence: 99%
“…Several works show that chronic exposure of insects, mainly those of the order Lepidoptera, to plant-derived protease inhibitors such as SKTI (Soybean Kunitz Trypsin Inhibitor), SBBI (Soybean Bowman-Birk Inhibitor), APTI (Adenanthera pavonina Trypsin Inhibitor), ILTI (Inga Laurina Trypsin Inhibitor) showed negative effects on the larval cycle of these herbivores (Figure 3). These adverse effects include reduced weight, survival, and delayed larval cycle [17,29,[71][72][73][74][75]. However, the use of these molecules so far in agriculture has not proven effective, mainly due to the long exposure period required to cause effective control rates.…”
Section: Trypsin-inhibition Focus For the Pest Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, given the abovementioned adaptive mechanisms exhibited by Lepidopteran insects when exposed to PIs type proteins, minor and specific molecules have been proposed as inhibitors of their main proteases in the gut (Chen et al, 2013; Meriño‐Cabrera, Castro, et al, 2020; Meriño‐Cabrera, de Oliveira Mendes, et al, 2020; Saikhedkar et al, 2019). In this investigation, we characterized of stability in silico by molecular dynamic (MD) and in vitro of the previously proposed tripeptides GORE1 (Val–Leu–Lys) and GORE2 (Val–Leu–Arg) (Barros et al, 2021).…”
Section: Introductionmentioning
confidence: 99%